Does External Beam Radiation Therapy Improve Survival Following Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma? - Cupino, Andrew C. (International Society of Gastrointestinal Oncology, 2012)
BACKGROUND: Transcatheter arterial chemoembolization (TACE) improves survival in patients with unresectable hepatocellular carcinoma (HCC). Partial liver radiotherapy with modern techniques has been shown to be safe. The purpose of this study was to evaluate the survival value of external beam radiation therapy (EBRT) with concurrent chemotherapy combined with TACE. METHODS: A University of Virginia Interventional Radiology patient log was used to identify patients treated with TACE ± another modality from 1999 through 2005. During this time, 44 patients received TACE for unresectable HCC, and 7 of these received adjuvant EBRT. Univariate analysis and multivariable proportional hazards survival modeling were used to identify factors impacting survival. RESULTS: We compared 37 patients receiving TACE alone to 7 receiving TACE and EBRT (5 with concurrent capecitabine). Unadjusted mean transplant-free survival times were TACE only = 376 days (standard error [SE] = 63 days), TACE + EBRT = 879 days (SE = 100 days). EBRT, TNM stage, and MELD score were important predictors for survival on univariate analysis (p < .10). The adjusted hazard ratio for transplant or death in the TACE + EBRT group was 0.15 (0.02–0.95, p = .026). CONCLUSION: EBRT with concurrent chemotherapy following TACE is feasible and well tolerated with modern treatment techniques. Further research should be directed toward determining the potential overall survival benefit of adjuvant EBRT with chemotherapy following TACE for hepatocellular carcinoma.